EVOLUSI BUDAYA ARTEFAKTUAL SUKU ASMAT DALAM PENDEKATAN EKOTEOLOGI - Anggraheni, Wina Sulistyo Nur; Prasodjo, Tjahjono (Universitas Negeri Gorontalo, 2023)
The Asmat tribe has experienced significant cultural and civilizational changes in two phases, namely the arrival of missionaries in 1953 and post-independence of Indonesia in 1963. The abolition of the head-hunting tradition carried out in the mission to